Cryptocurrency Market Dynamics: The Effect Of Bitcoin, Gold, Crude Oil, And IHSG Prices On Crypto Tokens And Altcoins - Tri Ayu Lestari; Euis Mufahamah; Hiro Sejati (Oikonomia : Journal of Management Economics and Accounting, 2026)
In recent years, crypto assets have grown rapidly and become increasingly well-known. Some view them as promising investment opportunities, while others consider them high-risk due to their sharp fluctuations. This situation prompted researchers to examine factors that could potentially influence cryptocurrency price movements, particularly macroeconomic variables often associated with changes in global financial market conditions. This study used monthly data from 2020-2024, covering the prices of Bitcoin, Gold, Crude Oil, the Jakarta Composite Index (JCI), as well as the price movements of Crypto Tokens and Altcoins. The analytical method used was multiple linear regression with purposive sampling. The results showed that the price of Bitcoin had a positive and significant effect on the prices of Crypto Tokens and Altcoins. Meanwhile, the price of Gold, Crude Oil, and the JCI did not have a significant impact. This finding confirms that changes in crypto asset prices are driven more by internal market mechanisms, such as supply and demand, than by macroeconomic indicators